Análisis de la cuenta ingresos y su repercusión en la productividad económica de la empresa De_Todo.Com de los periodos 2019 y 2020 - Ramos Solís, Cecilia de Jesús (2021)
This case study called "Analysis of the income account and its impact on the economic productivity of the company De_todo.com" follows the sub-line of research of financial management, tax and social commitment that allows us to have a knowledge approach with Regarding the study that we are going to develop and it focuses on the analysis of the income of the aforementioned company during the periods 2019-2020 through the horizontal analysis technique, through the absolute variation and relative variation to be able to know what the changes have been of the consecutive periods proposed, in order to identify the variations in the income accounts of the State of Comprehensive Results of the aforementioned periods and identify how the productivity of the company has been affected.